CAN AUTOMATIC POETRY GENERATION INFUSE VALUES? UNVEILING INSIGHTS THROUGH CONTENT ANALYSIS OF GENERATED POETRY - Yazid, S. Rizal; Mustofa, Mutmainnah; Fitriyah, Ulil (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2024)
This research examines the value underlying poetry created by artificial intelligence (AI), aiming to uncover the complex interaction of religious, philosophical, ethical, and aesthetic values presented in poetry. Eighteen poems generated by three different AI platforms were analyzed using the content analysis method to identify their social values. The results of this research demonstrate the presence of (1) religious values by revealing the AI’s ability to explore traditional and cultural barriers, highlighting themes of spirituality and faith, (2) philosophical values through the exploration of questions of human existence and the nature of reality, showing the AI's capacity to engage with deep existential themes, (3) ethical values by promoting concepts of unity, fairness, and justice, reflecting deeper humanistic perspectives and societal ideals, and (4) aesthetic values by showcasing an interest in the influence of technology and a profound admiration for the natural world's wonders, integrating modern innovation with timeless beauty. In conclusion, AI-generated poetry successfully captures a broad spectrum of human values, enriching literary traditions and intellectual discussions. This intersection of AI and poetry not only highlights technological advancements in creative fields but also opens new avenues for exploring how machines can contribute to cultural and artistic expressions, fostering a deeper understanding of the human condition and societal values.